Social Factors Leading to Code Switching in Oral Expression among Female Students in Qassim University - Alostta, Ruqayah lbrahim (Journal of Humanities & Social Sciences, 2022)
This study aimed at identifying the features of bilingual verbal expression in Saudi Female students and to identify the causes and social factors of the phenomenon of bilingual oral expression in Female students in order to reach proposed solutions for the treatment of bilateral oral expression. The researcher adopted the descriptive approach, and her it is tool is questionnaire and a sample of 377 students. It was clear from the results of the study that the role of the family is weak in the use of girls to express bilingual oral and mixing English terms talking in Arabic words, and that girls who study in the disciplines of legitimacy more inclined to imitate the father and mother in the bilateral verbal expression they use some foreign terms in their words with others, and that scientific specialization especially applied science has the power to determine the direction of the university girl in imitating her mother and sister in verbal expression.The effectiveness of media and cultural friction has also been shown to be high in girls' use of oral and verbal expression and their mixing of English and Arabic, It also showed that the role of employment and employees is average in the use of girls to express oral and verbal mixing of English terms in Arabic, the effectiveness of media and cultural friction has also been shown to be high in girls' use of oral and verbal expression and their mixing of English and Arabic, It was also found that girls at the higher economic level and in the culture of large cities were more inclined to speak in the bilingual language of oral expression while traveling. They entered some foreign terms in their conversation with others.
Keywords: Social Factors; oral expression; English terms